Amyotrophic lateral sclerosis: a comparison of two staging systems in a population‐based study. (30th May 2016) - Ferraro, D.; Consonni, D.; Fini, N.; Fasano, A.; Del Giovane, C.; Mandrioli, J.
Abstract : Background and purpose: To compare two recently developed staging systems for amyotrophic lateral sclerosis (ALS) [King's College and Milano‐Torino staging (MITOS) systems] in an incident, population‐based cohort of patients with ALS. Methods: Since 2009, a prospective registry has been recording all incident cases of ALS in the Emilia Romagna region in Italy. For each patient, detailed clinical information, including the ALS functional rating scale score, is collected at each follow‐up. Results: Our study on 545 incident cases confirmed that King's College stages occurred at predictable times and were quite evenly spaced out throughout the disease course (occurring at approximately 40%, 60% and 80% of the disease course), whereas MITOS stages were mostly skewed towards later phases of the disease. In the King's College system there was a decrease in survival and an increase in deaths with escalating stages, whereas in the MITOS system survival curves pertaining to intermediate stages overlapped and the number of deaths was fairly homogenous throughout most stages. Conclusions: The King's College staging system had a higher homogeneity (i.e. smaller differences in survival among patients in the same stage) and a higher discriminatory ability (i.e. greater differences in survival among patients in different stages), being more suitable for individualized prognosis and for measuring efficacy of therapeutic interventions.